Representasi Self Control Dalam Meminimalisasi Internet Addiction - Ardiati, Syarifah Setiana; Bassar, Agus Samsul; Yuliana, Deta Ginanjar (Prodi PAI IAILM Suryalaya, 2024)
One of the factors that influence the level of internet addiction is the low level of self-control. This study aims to determine the level of self-control, the level of internet addiction and to determine the effect of self-control on students' internet addiction. The method used in this research is descriptive method through a quantitative approach. The population is all students of MTs Islamiyah Ciawi Tasikmalaya with a total of 167 people. While the sample is 35 people. The sampling technique used is Simple Random Sampling. While the data collection techniques used are observation, questionnaires, documentation and interviews. The data analysis technique for each variable uses the arithmetic mean, while the correlation analysis for the two variables uses the Spearman rank correlation (rs). Data analysis of students' level of self-control is in the good classification with an average count of 52.37 and data analysis of students' internet addiction level is in the low classification with an average count of 39.17. While the correlation analysis of the effect of self-control on internet addiction of students at MTs Islamiyah Ciawi Tasikmalaya is in the High classification with an Rs value of 0.80 in the interval 0.61 - 0.80. With the degree of determination obtained from the indicators of self-control and internet addiction, students at MTs Islamiyah Ciawi Tasikmalaya are 64% and 34% are determined by other factors outside of the study. The results of the hypothesis test obtained t count of 7.656 > t table 1.692360. This means that the alternative hypothesis (Ha) which states that there is a significant influence between the level of self-control on students' internet addiction at MTs Islamiyah Ciawi Tasikmalaya is accepted and the null hypothesis (Ho) is rejected.